Neurodevelopment and growth outcome at one year in babies born at term to mothers having pregnancy induced hypertension - Pagali, Deepthi; Bollipo, Suneetha; Natta, Srinivasa Vithal Rao (International Journal of Contemporary Pediatrics, 2018)
Background: Hypertensive disorder in pregnancy remains an important cause of perinatal morbidity and mortality. Being small for gestational age (SGA) may be associated with poor neurodevelopmental outcomes compared to being appropriate for gestational age (AGA). The aim of this paper is to evaluate neurodevelopmental scores as well as growth monitoring in SGA and AGA infants born at term to PIH mothers followed till one year of age. Methods: This is a prospective, observational, hospital-based study, conducted in a tertiary care mother and child institute in Andhra Pradesh, South India. Results: Two hundred babies born at term to PIH mothers are included in the study and are followed up over a period of 12 months. Data is analyzed using Statistical Package for Social Sciences (SPSS). Growth retardation is seen in 12 % of term, SGA and 3.5% of term, AGA babies. SGA babies have a statistically significant correlation (p value = 0.02) in physical growth compared to AGA babies. Neurodevelopmental delay is present in 30% of SGA babies and 5% of AGA babies. The association between SGA and neurodevelopmental disability is statistically significant (p value <0.01). Conclusions: Pregnancy induced hypertension has a statistically significant effect on neurodevelopment and physical growth of a child when followed up to 12 months of age, in SGA babies, more so in VLBW babies. Early intervention programmes through medical, developmental, neuromotor, neurosensory interventions and other stimulation programs, might help in reducing the burden of the disease as well as improving the quality of life.